Evaluation of recombinant endostatin in the treatment of atherosclerotic plaques and neovascularization in rabbits - Mao, Wei (Zhejiang University Press, 2010)

(untitled)
Objective: Atherosclerotic plaques and neovascularization play an important role in the course of coronary atherosclerosis. This study evaluated the effect of recombinant endostatin on experimental atherosclerotic plaques and neovascularization in rabbits. Methods: Eighteen healthy male rabbits were divided into three groups: control group, atherosclerotic model group, and recombinant endostatin treated group. The atherosclerotic model was established via a high-cholesterol diet after balloon catheter injury. The subject weights, serum total cholesterol, creatine kinase-myocardial band fraction (CKMB), and matrix metalloproteinase-2 (MMP-2) were measured. Six weeks after treatment, the aortic roots were taken for pathological assay. The thickness ratio of the intima to media was measured by hematoxylin and eosin (HE) staining, and the number of neovessels was measured by immunohistochemistry via monoclonal antibody CD31 staining. Results: The weight, plasma total cholesterol, and CKMB were not significantly different between the atherosclerotic model group and the recombinant endostatin treated group, but much higher than those of the control group (P<0.05). The thickness ratio of the intima to media in the recombinant endostatin treated group was distinctly less than that in the atherosclerotic model group (P<0.05). The number of neovessels decreased dramatically (P<0.05) and the content of MMP-2 decreased slightly without statistical difference (P>0.05) in the recombinant endostatin treated group, compared to the atherosclerotic model group. Conclusions: Recombinant endostatin is able to inhibit the growth of neovascularization in the atherosclerotic plaque and the development of plaque.